Psychometric validation of the breast cancer treatment outcome scale (BCTOS-12): a prospective cohort study - Feißt, Manuel; Heil, Jörg; Stolpner, Ilona; Au, Alexandra von; Domschke, Christoph; Sohn, Christof; Kieser, Meinhard; Rauch, Geraldine; Hennigs, André (Archives of gynecology and obstetrics, 2019)
The Breast Cancer Treatment Outcome Scale (BCTOS) is a questionnaire to evaluate the aesthetic and functional outcome after breast conserving surgery (BCS). The original BCTOS with its 22 items on three subscales was refined to a shorter, improved, and easier to administer patient-reported outcome measure, the BCTOS-12. The BCTOS-12 consists of 12 items on two distinct subscales, the Functional Status and the Aesthetic Status. The aim of this study was to validate the BCTOS-12 in a prospective cohort.
Gesehen am 16.01.2020